Pengaruh Kompensasi Terhadap Kinerja Karyawan Bagian Sales Pada PT. Agung Toyota Kota Jambi - Meyna Fairuz Athaya (Science of Management and Students Research Journal (SMS), 2019)
The purpose of this research is to find out how employee performance compensation and part sales at PT Agung Toyota city of Jambi and to see the influence between the compensation on performance, with a successful research is expected to deliver input to the Great City of Toyota PT Jambi in order to make the company better.This research is quantitative desciptive research and a simple linear regression analysis is a tool used in the study are useful to see the direction of the relationship between the variables bound to the variable free. To answer the objective number 2 used the t test statistic. The correlation coefficient to find out how the relationship between variables and coefficient of determination is useful to see the magnitude of the influence of variables bound against free variables.PT Agung Jambi City Toyota is one of the companies engaged in the automotive industry, sales and service of toyota brand cars. The company offers a product that has the characteristics and adventagges compared to other types.SPSS calculations Y = 0.439 30.139 + X + e based on the equation, visible between compensating positive influence (X) against performance (Y) on the PT Agung Toyota city of Jambi. From the results of SPSS r2 (coefficient) values obtained this figure of 0.244 stated that compensation (X) are able to explain the performance variable (Y) is 24.4% and 75.6% the rest is explained by other factors not included in the study models. Compensation at Toyota Great PT Jambi City are on a very high criteria and performance of employees at PT Agung Jambi City Toyota is at a very high criteria. Compensation of positive and significant effect on performance in the great city of Toyota PT Jambi.